Reasons for conflicts between the employees in software in industry - Kiran Kumar Thoti; Roselina Ahmad Saufi; Bhavesh Rathod (2013)
Conflict refers to some form of friction, disagreement, or discord arising within a group when the beliefs or actions of one of more members of the group are either resisted by or unacceptable to one or more members of another group. Conflict can arise between members of the same group, known as intragroup conflict, or it can occur between members of two or more groups, and involve violence, interpersonal discord, and psychological tension, known as intergroup conflict. Conflict in groups often follows a specific course. Routine group interaction is first disrupted by an initial conflict, often caused by differences of opinion, disagreements between members, or scarcity of resources. At this point, the group is no longer united, and may split into coalitions. This period of conflict escalation in some cases gives way to a conflict resolution stage, after which the group can eventually return to routine group interaction once again.